HORMONE REGULATION OF GLYCERONEOGENESIS - Moreno, Franciele Neves (2012)
Glyceroneogenesis is the metabolic pathway which causes the conversion of pyruvate, lactate and aminoacids, mainly alanin, into glycerol-3-phosphate (G3P), especially during fasting, and thus guarantees the synthesis of triacylglycerols (TAG). Cytosolic phosphoenolpyruvate carboxykinase (PEPCK-C) is its key enzyme and is currently thought to be a restrictive mechanism to lipolysis, moderating the formation of ketone bodies and thus acidosis. The pathway lies in the white and brown adipose tissue and also in the liver. It may be important for the solution of human obesity and Type II diabetes. Current research analyzes the hormone factors, such as insulin, glycocorticoids, glucagon, epinephrine, norepinephrine and β-adrenergic agonists, which are the main pathway’s regulators. The sympathetic nervous system also participates in the regulation although it is a response caused by metabolic and hormonal factors. Further, other factors also partake of glyceroneogenesis control, such as cytokines or adipokines, since they decrease PEPCK-C’s gene expression and thus glyceroneogenesis. However, they cause an increase in AGL. The regulation of glyceroneogenesis depends on the subject’s metabolic state and on the type of tissue and organ in which it occurs, mainly by PEPCK-C regulation.